A high effective expression of human D-glucuronyl C5-epimerase with dimer structure in Escherichia coli - Song, Qin-xia; Guo, Li-jian (Frontiers in Microbiology, 2025)
IntroductionHeparan sulfate (HS), a linear anionic polysaccharide, participates in many physiological processes and exhibits many pharmacological activities. D-glucuronyl C5-epimerase (Glce) is one of the key enzymes in the biosynthesis of heparan sulfate proteoglycans. However, the recombinant Glce protein exhibits reduced catalytic activity and production yield, which substantially impedes the development of enzymatic methods for producing pharmaceutical-grade heparin.MethodsIn this experiment, we established a valid method for heterologous expression in Escherichia coli (E. coli) and subsequent purification of two N-terminal truncated Glce proteins using the SUMO-fused expression system. Characterization of human Glce167-617 was described by dynamic light scattering size-exclusion chromatography, and X-ray crystallographic.ResultsIn the present study, we successfully overexpressed and purified human Glce167-617 protein in E. coli. Subsequently, the recombinant Glce167-617 was found to exist as a dimer in solution. X-ray crystallographic result further confirmed its dimeric assembly while maintaining the integrity of the catalytic domain.DiscussionIn summary, this study successfully overexpressed and purified human Glce protein in E. coli. The purified Glce protein will be applied to chemoenzymatic synthesis of heparin and heparan sulfates in vitro, which facilitating the future bioengineering of pharmaceutical heparins.